KAJIAN LITERATUR : PERAN PERAWAT KOMUNITAS DALAM PENINGKATAN KEPATUHAN MINUM OBAT OAT PADA PASIEN TUBERKULOSIS DI LAHAN BASAH - Siregar, Yaumil Hafsani (Poltekkes Kemenkes Medan, 2025)
Tuberculosis is a chronic, infectious disease caused by the bacterium Mycobacterium tuberculosis, which can cause respiratory problems. Therefore, to prevent the risk of developing TB, regular medication intake is essential for tuberculosis patients. Non-adherence to treatment in pulmonary TB patients is influenced by several factors, one of which is nurses. Community nurses emphasize health promotion and prevention activities as crucial. The environment is one contributing factor to the disease, in this case. Wetlands are considered a source of disease, such as mosquito breeding grounds, leading to the spread of many diseases, such as malaria, dengue fever, yellow fever, and other wetland-related diseases. This literature review aims to examine the role of community nurses in improving adherence to anti-tuberculosis medication in patients with tuberculosis in wetlands. Articles were searched using databases including PubMed and Google Scholar, with the following inclusion criteria: full-text articles, published between 2014 and 2025, and with a DOI. The literature search revealed that community nurses play a crucial role in improving adherence to anti-tuberculosis medication management in TB patients. Furthermore, the effectiveness of OAT drug management in TB patients is also supported by nurses as healthcare workers and families as the smallest community unit involved in TB patient care.